2013
DOI: 10.1186/bcr3559
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of recurrence of early breast cancer is different according to intrinsic subtype and proliferation index

Abstract: IntroductionRecurrence risk in breast cancer varies throughout the follow-up time. We examined if these changes are related to the level of expression of the proliferation pathway and intrinsic subtypes.MethodsExpression of estrogen and progesterone receptor, Ki-67, human epidermal growth factor receptor 2 (HER2), epidermal growth factor receptor (EGFR) and cytokeratin 5/6 (CK 5/6) was performed on tissue-microarrays constructed from a large and uniformly managed series of early breast cancer patients (N = 1,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 48 publications
9
66
2
2
Order By: Relevance
“…The Ki-67 index value provides useful prognostic information beyond the traditionally assessed clinicopathological variables. It was reported that the Ki-67 index value was an independent prognostic factor in early breast cancer, particularly luminal type tumors (8,23). A multivariate analysis by Reyal et al (18) revealed that the Ki-67 index value remained the only significant prognostic factor in the subgroups of ER-positive and HER2-negative tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The Ki-67 index value provides useful prognostic information beyond the traditionally assessed clinicopathological variables. It was reported that the Ki-67 index value was an independent prognostic factor in early breast cancer, particularly luminal type tumors (8,23). A multivariate analysis by Reyal et al (18) revealed that the Ki-67 index value remained the only significant prognostic factor in the subgroups of ER-positive and HER2-negative tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the molecular types of IDCs [47], we observed that the luminal B subtype was less frequent in the group of smokers (6/39 vs 52/202), near statistical signifi cance (p=0,099), relationship increased when compared nonsmoker subgroup with active and former smokers subgroups together (7/50 vs 53/202; p=0,068). Although several groups have described that some of the substances found in cigarette act like estrogens, smoking has been postulated to have antiestrogenic effect and this would explain our fi ndings also that smoking is associated with an increased occurrence of hormone-receptor negative tumors [48], especially when the patients starting to smoke at an early age of </= 19 years [49,50].…”
Section: Discussionmentioning
confidence: 83%
“…Dzięki zastosowaniu 5-letniego leczenia tamoksyfenem bezwzględne 10-letnie ryzyko nawrotu zostało obniżone o około 15%, co z kolei przełożyło się na 10-procentowe obniżenie 15-letniego ryzyka zgonu [1]. W przeciwieństwie do raków pozbawionych ekspresji receptorów steroidowych, w których większość nawrotów pojawia się w ciągu pierwszych kilku lat po leczeniu, wznowy raków luminalnych wystę-pują jednak często po wielu latach, a roczne ryzyko nawrotu utrzymuje się na prawie stałym poziomie przez wiele lat [2,3]. U chorych leczonych uzupełniająco przez 5 lat ponad połowa nawrotów pojawia się po upływie pierwszych pięciu lat od rozpoznania raka piersi [4].…”
Section: Elżbieta Senkus-konefkaunclassified